Propuesta de un manual de funciones, descripción de cargos y reglamento de ingresos y empleo para el departamento de talento humano en la empresa Practipower en la ciudad de Guayaquil - Yánez Jiménez, Manuel Vladimir Yánez Jiménez (2016)
This work has the general objective to develop a manual of functions , positions and description of income and employment regulations for the Department of Human Resource in Practipower Company in the City of Guayaquil , so efficiency will be achieved in the performance of functions assigned to the staff and the proper selection of company personnel , to meet this objective the following methods as deductive , inductive, historical, descriptive used ; as well as observation technique with which data were collected about the development activities of the company. An interview was conducted by Manager of the company with which it was possible to collect information about historical and general company data identifying the beginning of operation in the city of Guayaquil and setting the number of employees their administrative and operational levels, which allowed perform internal analysis at the administrative level, identifying the reality in which the administration of human talent is, showing that lack a defined and established organizational structure. The internal analysis a survey was applied to the 26 employees of the company, identifying the problems and benefits offered by the company. Based on this analysis we proceeded to review the most relevant terms of the administrative and operational staff and proposed the development of a Manual of Functions, description of charges and income and employment regulation is presented. The design manual functions at management and operational levels, defining the job title, summary charge, relationships, roles and responsibilities. The proposed regulation of income and employment, identifies four stages to be followed for recruitment, either internally or externally of the company, taking as an example the scheme established by the Ministry of Labour Relations, because as strategy, the company must publish their processes internally and externally. The selection process involves 11 procedures, contracts stipulating the minimum time staff of 30 days and maximum 50 days , induction and integration of personnel will be the responsibility of the Head of Talent in coordination with the chief of staff requesting the contracted area . Finally , the company Practipower is recommended to implement this proposal , which will ensure the allocation of functions and avoid duplication thereof, and to establish the rules and procedures to be followed for recruitment to internal and external level administrative and operational areas achieving efficiency and effectiveness in all functions.